Education integrity survey: A suggested measurement of integrity in education sector (Integritas : Jurnal Antikorupsi, 2022)
Integrity as a concept is usually associated with and measured by one of two separate scopes: personal or organizational. This paper argues that in educational institutions such as schools or universities, integrity measurement should not be done by separating personal and organizational concepts. In addition, integrity in education sector is often discussed just from academic perspective such as cheating, plagiarism or other wrongdoings in classroom or research activity. The measurement concept in this paper also includes non-academic aspects such as administrative services, financial management, and procurement. Educational integrity in this paper combines three concepts which are the character dimension (Istiani, 2015), the Corporate Ethical Value model (Kaptein, 2007), and the classification of corrupt behaviors in education compiled by KPK from various resources (2018). To conclude, the concept of educational integrity should be looked as holistic one which can be assessed from the integrity character of students, the ecosystem that influences them, and also the compliance level of school’s governance. This offered concept tries to fulfill the strategic role in encouraging educational stakeholders to massively and systematically evaluate the achievement of integrity improvement in the education sector, including the human capital result.